Electrocatalytic detection of herbicide, amitrole at WO3·0.33H2O modified carbon paste electrode for environmental applications - Ilager, Davalasab; Seo, Hyungtak; Shetti, Nagaraj P.; Kalanur, Shankara S.; Aminabhavi, Tejraj M. (Science of the Total Environment, 2020)
Environmental pollution by the heavy usage of pesticides has been a pandemic issue in view of the rising farming operations for increasing the crop yield to meet the requirements of food chain supply. Throughout the world, environmental pollution by the presence of pesticides, particularly the use of herbicides in large quantities to protect the crops, has posed many environmental issues. In this research, an electrochemical sensor based on tungsten oxide hydrates (WO3·0.33H2O) nanorod modified carbon paste electrode (CPE) was developed for the detection of herbicide, amitrole (AMT) by the cyclic voltammeter. Hydrothermally synthesized and characterized WO3·0.33H2O nanorod was found to be sensitive towards the detection of AMT due to its superior sensing property as the sensor showed enhanced current and catalytic property when used in phosphate buffer solution (PBS) of pH 5.0 by the cyclic voltammetric (CV) and square wave voltammetric (SWV) techniques. The influence of electro kinetic parameters viz., scan rate, pH, accumulation time and temperature with respect to AMT oxidation was studied using CV. The linearity range was in between 1.0 × 10−8 M and 24 × 10−5 M and limit of detection (LOD) and limit of quantification (LOQ) was calculated to be 2.33 nM and 7.8 nM respectively. The proposed simple method demonstrated the potential applicability to detect AMT from the soil and water samples.
Keywords: Catalytic properties; Environmental applications; Environmental issues; Environmental pollutions; Hydrothermally synthesized; Limit of quantifications; Modified carbon paste electrode; Phosphate buffer solutions; Amitrole; Electrochemical oxidation; Environmental applications; Herbicides; Temperature effect; Voltammetric determination